Chinese consumers do not always respond to red: The influence of colors on perceived distance, spaciousness, and purchase intention of Chinese consumers - Zhao, Dan; Guan, Fengwei (Frontiers in Psychology, 2023)
Many international firms hold a common stereotype about Chinese consumers’ color preference: culturally, red is their favorite color. However, many international firms (e.g., P&G, Ford, and Wal-Mart) do not use red as their theme colors when they run business in the Chinese market. To explain this interesting phenomenon, this study conducted three which include one IAT experiment and two scenari-based experiments to reveal less culture-laden influences of colors on people by examining the mediating effects of perceived spaciousness between colors and purchase intention. The results show that blue walls of a room make the room look more spacious than red ones and eventually increase consumers’ purchase intention. The perceived spaciousness is caused by the fact blue objects are perceived more distant than red ones. The findings indicate that culturally favorable color may not always be the most effective tool to increase consumers’ purchase intention. Hence, international firms should be extremely cautious when selecting a theme color in foreign markets.